Listening and feeling doctoral students’ perceptions of their doctoral supervision. The PhD students’ point of view. - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2020)
Doctoral education has been subject to research and analysis by researchers in the last fifty years. Nevertheless, doctoral supervision still a private issue among supervisor and PhD student; if the relationship between them goes wrong, a shadow undermines the doctoral research, hindering student support of others, which may result in attrition and dropout. Breaking this situation, transforming the “private place” in a “public matter”, requires a profound reflection about the doctoral education aim, institutions goals, institution policy, but also a supervisor and PhD students’ perspectives (careers, goals, development, financial support). It is necessary to know, where we want to go, to outline a path to achieve the goals. During the last three years, doctoral supervision has been studied at Universidade Nova de Lisboa (UNL). A qualitative case study method was used. This was the first study (a pilot study) that covered all the nine UNL schools, is intended to identify the supervision practices, but also captures a glimpse of doctoral students’ life in the academy, their difficulties, their thoughts and feelings related to doctoral education. The documentary analysis, concerning the institution rules related to doctoral education, was the study first step (already published). The second was the implementation of a survey with closed and open questions to allowed students to express their opinion regarding doctoral education, especially doctoral supervision. During three months, a survey, centred in doctoral supervision, applied online in all schools. This paper aims to describe what was found and what was unexpected in the context of a young university.